Notes on little known Tortricid mothsfrom Central-Southern Italy with record of Cnephasia hellenica Obraztsov, 1956, new far the Italian fauna (Lepidoptera Tortricidae). (Bollettino di zoologia agraria e bachicoltura, 2024)
Remarks on some interesting and litte known tortricid moths species, collected in Central-Southem Italy, were reported. The presence of Cnephasia hellenica Obraztsov, 1956, in Italy is recorded; the species was found in Molise region, at the mouth of Torrente Saccione, Campomarino (Campobasso).
Keywords: Lepidoptera Tortricidae; faunistic records; Cnephasia hellenica; Italy